Usability and Accessibility Framework for Digital Libraries - King, Neil; Hoi-Yan Ma, Terry; Zaphiris, Panayiotis; Petrie, Helen; Hamilton, Fraser (My University, 2003)
Libraries have always tried to remove obstacles to information access. A poorly designed digital library (DL) is certainly a barrier to users; therefore the need exists for a specific usability and accessibility framework for the design and evaluation of DL’s, which if adopted can help ensure enhanced usability of a service. The framework consists of three stages - query techniques, user testing and expert evaluations, and embodies the need for assessment after each stage. The framework also defines the techniques and methodologies to be conducted at each of these stages. Usability and accessibility evaluations of four DL services clarified our view that the specific dimensions of these services can be better evaluated via the adoption of this framework.